Understanding Followership: A Literature Review - Triyo Utomo; Seger Handoyo; Fajrianthi Fajrianthi (International Journal Labs, 2022)
Followership has started to become the center of attention of scholars since several decades ago. The promotion of the followership concept was first echoed by Kelley in the Harvard Business Review in 1988. In order to understand more about followership, it helps to learn more about the various meanings of followership from social scientists. Based on these considerations, this study aims to synthesize and evaluate the notions of followership, both from the trait and state perspective. The method used in this study is a literature review by conducting a scoping review of various previous studies in order to answer the current research objectives. First of all, we define the search protocol. The next step is to do a thematic analysis based on the results of the search protocol. The results show that there are four main themes related to the notion of followership. The four themes are followership as a role and positional behavior, followership as personal characteristics and abilities of followers, followership as a process and condition of being a follower, and followership as a macro perspective. In the context of the trait and situational approach, there is a difference in the meaning of followership. The trait approach emphasizes the personal characteristics of followers, while the state approach focuses on the role and position, the followers' abilities, and the processes and conditions of being a follower. The conclusion that can be drawn from the findings of this scoping review is that the concept of followership has a broad understanding and has an impact on the scope of the research results. The next conclusion relates to trait and state approach, which has its own implications for its emphasis on the followership definition.